Assessing the efficacy of natural soil biotin on soil quality, microbial diversity, and Rhododendron simsii growth for sustainable landscape architecture - Teng, Zhiyan; Chen, Lan; Li, Sheng; Pan, Kexuan; Liu, Dandan; Gu, Zaiyuan; Wang, Yijie; Huang, Li; Chen, Yunwen (Frontiers in Microbiology, 2024)
Fertilization exerts a profound influence on soil quality and its sustainable utilization. In urban garden maintenance, the prevalent use of inorganic fertilizers has been associated with ecological concerns. Conversely, organic fertilizers, though beneficial, often exhibit slow efficacy and high costs.Biofertilizers, characterized by their eco-friendly attributes and low carbon footprint, play a multifaceted role in supporting plant growth. Thus, optimizing the application of biofertilizers and investigating their potential as substitutes for inorganic and organic counterparts remain imperative for sustainable landscape architecture. While prior investigations have primarily concentrated on fruit trees, vegetables, and medicinal plants, few have been on ornamental plant species. In this study, the Rhododendron plants Azalea hybrid 'Carnation' was selected to assess the efficacy of a novel microbial fertilizer termed 'natural soil biotin'. Changes in soil properties, microbial diversity, enzyme activity, plant morphology, and physiological parameters were measured following fertilizer application to compare the impacts of various fertilization strategies. The results showed that the combined use of natural soil biotin effectively enhanced soil properties, mitigated the influence of both inorganic and organic fertilizers on soil pH, and improved the relative abundance of Proteobacteria, Ascomycota, and Basidiomycota. Additionally, this mixed application significantly elevated the activities of urease and sucrase in Rhododendron plants, thereby promoting their growth, development, and resistance to stress. Therefore, the mixed application of natural soil biotin significantly improved the efficiency of utilizing inorganic and organic fertilizers, leading to enhanced economic and environmental benefits in Rhododendron cultivation and laying a foundation for soil improvement and ecological restoration.